(untitled) (Italian Journal of Public Health, 2006)
Background: Opioid abuse and dependence are major health and social issues in most societies. Different interventions are available, but the majority of heroin patients relapse and these relapses are a substantial problem to their rehabilitation. Psychosocial interventions for drug addicts have been suggested as possible instruments to overcome the difficulty of maintaining a drug-free state. The aim of this paper is to provide a summary of the available evidence of effectiveness. Methods: We summarised the results from two systematic reviews on psychosocial interventions combined with Methadone Maintenance Treatment and Methadone or Buprenorphine Detoxification Treatment. Results: For detoxification treatments, the results show that benefits can be gained from adding any psychosocial treatment to any substitution detoxification treatment in terms of completion of treatment: relative risk (RR) 1.68 (95% CI 1.11-2.55), and compliance (proportion of clinical absences): RR 0.48 (95% CI 0.38-0.59); for the use of heroin during treatment, the differences were not statistically significant. For maintenance treatments, there is an additional benefit to be gained in adding any psychosocial treatment to methadone maintenance treatment in relation to the use of heroin during treatment: RR 0.69(95% CI 0.53-0.91); no statistically significant additional benefit was shown in terms of treatment retention and results at follow-up. Conclusions: Psychosocial treatments offered in addition to pharmacological detoxification treatments are effective in terms of completion of treatment and compliance, while adding any psychosocial support to methadone maintenance significantly improves the non-use of heroin during treatment but does not improve the other outcomes considered